IMPLEMENTATION OF THE TRANSPORTASIKU SYSTEM POLICY TO EASY PUBLIC TRANSPORT INFORMATION IN THE CITY OF SURABAYA - Prasetijowati, Tri; Wahyulila, Anisa Nur (DIA: Jurnal Administrasi Publik, 2021)
The research aims to find out the implementation of Transportasiku system policy in providing easy transportation information to the public in the Surabaya city area through one application, the factors that hinder the implementation of this Transportasiku System policy, and the efforts in dealing with obstacles to the implementation of the policy. The research method used is a type of qualitative research. Informants in this study are the officials who are responsible for the manufacture of Transportasiku, the developer of Transportasiku and the public who use Transportasiku. The data collection techniques used is with interviews and documentation. The techniques used in data analysis is data reduction, data presentation, and drawing conclusions. The results of the research show that: 1) The implementation of Transportasiku system policy to facilitate public transportation information in the city of Surabaya like communication, disposition, and bureaucratic structure. 2) The factors that hinder the implementation of the policy are limited human resources, limited available budgetary resources, limited equipment to support the implementation of the policy, and the occurrence of system errors when Transportasiku system underwent maintenance. 3) The efforts of the Department of Transportation in this case is the division of tasks and the quality of qualified human resources and good performance of existing human resources, to manage the availability of budget resources, to take advantage and do maintenance facilities available periodicly, and perform a reset or system development so that problems with the use of Transportasiku System can be resolved.